Arthroscopic approach to the spring (calcaneonavicular) ligament. Issue 3 (June 2018) - Lui, T.H.; Mak, C.Y.D.
Highlights: An accessory medial portal allows arthroscopic access of the spring ligament. Arthroscopic approach and repair of the spring ligament can injure the medial plantar nerve. Ligament repair using the outside in technique may be less risky to the medial plantar nerve than the inside out technique. Abstract: Background: This research studied the safety and efficacy of a new portal to the spring ligament. This portal is located just plantar to the insertion of the posterior tibial tendon and above the fibrous septum between the posterior tibial and the flexor digitorum longus tendons. Methods: Twelve fresh frozen foot and ankle specimens were used. The distance between the accessory medial portal and the medial plantar nerve was measured. The relation between the medial plantar nerve and the spring ligament was studied. The depth that can be reached through the portal was also assessed. Results: The average distance between the insertion point of the 3 mm diameter metal rod and the medial plantar nerve was 20(6–27) mm. The medial plantar nerve located at lateral third of the ligament in 8 specimens (67%), middle third in 2 specimens (17%) and medial third in 2 specimens (17%). The tip of rod can reach Zone A in all specimens. Conclusion: This study demonstrated that arthroscopic approach and repair of the spring ligament can injure the medial plantar nerve. Clinical relevance: The clinical relevance of this cadaver study is that it confirmed the feasibility of arthroscopic approach to the whole span of the spring ligament and alerted the potential risk of injury to the medial plantar nerve during arthroscopic assisted repair of the ligament.